2016
DOI: 10.1371/journal.pone.0148990
|View full text |Cite
|
Sign up to set email alerts
|

Does Marriage Make Us Healthier? Inter-Country Comparative Evidence from China, Japan, and Korea

Abstract: ObjectivesThis study focuses on East Asian countries and investigates the difference in the marriage premium on the health-marriage protection effect (MPE) between younger and older generations and the intra-couple education concordance effect (ECE) on the health of married individuals. This study used inter-country comparative data from China, Japan, and Korea.MethodsThis study focused on individuals (n = 7,938) in China, Japan, and Korea who were sampled from the 2010 East Asian Social Survey. To investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 24 publications
1
32
0
4
Order By: Relevance
“…Marital status and living arrangement are other important factors influencing the mental health of the elderly. Our study showed that single/divorced/widowed persons and those living alone were more likely to suffer from mental problems, which are consistent with the findings from other studies [30,32,33]. In addition, this may be attributed to the changes of family structure from a multi-child family to a single-child one.…”
Section: Discussionsupporting
confidence: 92%
“…Marital status and living arrangement are other important factors influencing the mental health of the elderly. Our study showed that single/divorced/widowed persons and those living alone were more likely to suffer from mental problems, which are consistent with the findings from other studies [30,32,33]. In addition, this may be attributed to the changes of family structure from a multi-child family to a single-child one.…”
Section: Discussionsupporting
confidence: 92%
“…Many researchers concluded that marriage has a protective effect on mental health (Fu & Noguchi, 2016; Hughes & Waite, 2009). In our study, divorce or separation from one’s spouse is the most significant factor associated with psychological distress.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is assumable that marital status among the younger population may not result in better health and happiness. The diminishing role on better health outcomes in the context of progressive industrialisation and modernisation have been reported in several Asian countries as well (Fu and Noguchi 2016). As countries in Africa continue to embrace modern lifestyles and culture characteristics of Western countries, exploring the dynamics of family, marriage, and fertility can be rewarding in terms of promoting evidence for better psychosocial health of the population.…”
Section: Discussionmentioning
confidence: 99%